2008
DOI: 10.1136/thx.2008.099390
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposures and the risk of COPD: dusty trades revisited

Abstract: Background: The contribution of occupational exposures to chronic obstructive pulmonary disease (COPD) and, in particular, their potential interaction with cigarette smoking remains underappreciated. Methods: Data from the FLOW study of 1202 subjects with COPD (of which 742 had disease classified as stage II or above by Global Obstructive Lung Disease (GOLD) criteria) and 302 referent subjects matched by age, sex and race recruited from a large managed care organisation were analysed. Occupational exposures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
142
1
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(158 citation statements)
references
References 37 publications
9
142
1
6
Order By: Relevance
“…The studies comprised a total of 92 452 subjects. In some cases, a job-exposure matrix (JEM) was used to characterize the exposure (32)(33)(34)(35), while others use JEM jointly with an expert opinion (35) or a questionnaire (32)(33)(34). Use of record-defined (16 occupational categories) description of exposure was limited (40), while in 20 studies (36-39, 41-56) the exposure was self-reported and questionnaire-based.…”
Section: Population-based Studiesmentioning
confidence: 99%
“…The studies comprised a total of 92 452 subjects. In some cases, a job-exposure matrix (JEM) was used to characterize the exposure (32)(33)(34)(35), while others use JEM jointly with an expert opinion (35) or a questionnaire (32)(33)(34). Use of record-defined (16 occupational categories) description of exposure was limited (40), while in 20 studies (36-39, 41-56) the exposure was self-reported and questionnaire-based.…”
Section: Population-based Studiesmentioning
confidence: 99%
“…4,5 The heterogeneity of COPD may be due to the variations in genetic influences and environmental exposures among which exposures to biomass fuels and dusty jobs were reported to be related with the development of COPD in Asia. 6,7 Therefore, to assess the heterogeneity of COPD, it would be reasonable to compare the exposure history of biomass fuels and dusty jobs, demographic characteristics, and clinical characteristics of COPD patients from different cities or regions.…”
Section: Introductionmentioning
confidence: 99%
“…Existen estudios (Balmes et al, 2003;Govender, Lalloo y Naidoo, 2011;Hnizdo, Sullivan, Bang y Warner, 2002) que avalan el efecto de la exposición profesional entre trabajadores de muy diversas ocupaciones (industrias plásticas, textiles, manufactura de productos alimentarios, construcción, agricultura, limpieza profesional) y que la asociación de esta exposición con el tabaquismo aumenta aún más el riesgo de desarrollar EPOC (Blanc et al, 2009).…”
Section: Discussionunclassified